Experimental evaluation of all-optical asynchronous and synchronous memories - Reis, Cláudia (2010)
We experimentally demonstrate the accuracy of an all-optical S-R latch and an optical S-R flip-flop based on hybrid integrated Mach-Zehnder Interferometers, with Semiconductor Optical Amplifier in each arm (MZI-SOA). The performance of both bistable devices will be studied and compared in terms of extinction ratio and switching times.